Increased sIL-2Rα leads to obstruction of IL-2 biological function and Treg cells differentiation in SLE patients via binding to IL-2 - Long, Dan; Yu, Shujiao; Zhang, Lu; Guo, Yang; Xu, Shumin; Rao, Yuting; Huang, Zikun; Luo, Qing; Li, Junming (Frontiers in Immunology, 2022)
Background The decrease of IL-2 level is believed to play an important role in the disease occurrence and development of SLE, but the relevant mechanisms have not been fully clarified. Many studies have found that the level of soluble interleukin 2 receptor α (sIL-2Rα) in SLE patients is significantly increased. Considering the fact that sIL-2Rα has the ability to bind IL-2, we want to know whether the increased sIL-2Rα has some impact on the level and function of IL-2 in SLE patients. Methods New onset SLE patients, treated SLE patients and healthy volunteers were recruited. The levels of serum IL-2, IL-2 mRNA in CD3+ T cells and serum sIL-2Rα were detected and compared in these subjects. Two mixed solid-phase sandwich ELISA system were designed to measure exclusively the heterodimers complex of sIL-2Rα/IL-2. The sera from SLE patients were pretreated with or without immune complex dissociation solution and detected for IL-2 levels. IL-2 standard or serum from HCs were used to co-incubate with recombinant sIL-2Rα or serum samples with high levels of sIL-2Rα and detected for IL-2 levels by ELISA. The inhibitory effect of sIL-2Rα on IL-2 biological activity was investigated by CTLL-2 cell proliferation assay. The frequencies and absolute counts of Treg cells were detected by flow cytometry before and after the addition of recombinant sIL-2Rα. Results The levels of serum IL-2 in SLE patients were significantly decreased and negatively correlated with SLEDAI. However, there was no significant difference in IL-2 mRNA levels in CD3+ T cells between SLE patients and healthy controls. The levels of serum sIL-2Rα in SLE patients were significantly increased, positively correlated with the SLEDAI and negatively correlated with the levels of serum IL-2. sIL-2Rα was shown to bind to IL-2 to form immune complex, resulting in false reduction in the detection level of serum IL-2 and significant decrease in biological activity of IL-2. The increase of sIL-2Rα was demonstrated to be one of the important mechanisms for the obstruction of Treg cells differentiation in SLE patients. Conclusion Increased serum sIL-2Rα can bind to IL-2, leading to obstruction of IL-2 activity and Treg cells differentiation.